Work-related communicative profile of radio broadcasters: a case study. (2nd October 2019) - Cantor-Cutiva, Lady Catherine; Bottalico, Pasquale; Hunter, Eric
Abstract: Purpose: To explore the short-term effect of work-related voice use on voice function, and noise exposure on hearing function among radio broadcasters. Method: A 1-week follow-up study with the participation of two radio broadcasters was conducted. Participants were monitored at the beginning and at the end of the working week. Premonitoring assessment on Monday (baseline measure) and postmonitoring assessment on Friday (follow-up measure) were performed to identify short-term effects of work-related conditions on voice and hearing function among radio broadcasters. Result: Changes in fundamental frequency postmonitoring at the end of the work week may be an indication of work-related vocal fatigue. Changes in the distribution and standard deviation of SPL during the monitoring from Monday to Friday may indicate control of the vocal loudness as a strategy to reduce vocal effort during broadcasting. During a 1-week follow-up, noise conditions during radio broadcasting were below occupational exposure limits and without noticeable consequences on hearing function. Conclusion: The work-related communicative profile of radio broadcasting, from this pilot study, suggests that although vocal demands in terms of vocal load may differ among broadcasters, the work-related conditions of broadcasting may play a role on vocal function among these occupational voice users. Concerning hearing function, our results indicate that occupational noise exposure represented minimal risk for hearing problems but the consequences of long-term noise exposure on hearing mechanisms may yet occur. Future studies with bigger sample sizes are warranted to confirm our results.